Pengembangan e-LKPD Interaktif Materi Minyak Bumi Berbasis SETS-PBL Untuk Siswa Kelas XI SMA - Wulan Sari; Abudarin Abudarin; Fatchiyatun Ni'mah (Jurnal Ilmiah Kanderang Tingang, 2026)
This research is a development study (Research and Development) using the Lee & Owens development model. The resulting product is an Interactive e-LKPD on Petroleum Material Based on SETS-PBL. The research instruments consist of feasibility questionnaires and student response questionnaires. The feasibility test of the e-LKPD product was conducted by material and media experts from the Chemistry Education faculty and evaluated by Chemistry teachers at SMA Negeri 2 Muara Teweh. Data on student responses were collected from the eleventh grade at SMA Negeri 2 Muara Teweh involving 25 students. The research results show that the developed e-LKPD product received a total score of 93 from media experts with an average of 4.8, classified as "Very Suitable." The evaluation from content experts yielded a total score of 47 with an average of 4.7, categorized as "Very Suitable." Based on the assessment instrument results from teachers towards the developed e-LKPD, a total score of 62 was obtained with an average score of 4.1, categorized as "Suitable." Additionally, the calculation of student responses indicated a respondent answer percentage of 87.68%, with criteria of "Very Good," indicating that the SETS-PBL based e-LKPD developed has met the standards with good quality.